Hieracium s. str. species from the Balkan Peninsula: secondary metabolites and pharmacological potential - Milutinović, Violeta (Archives of Pharmacy, 2022)
The hawkweed genus Hieracium L. s. str. (Asteraceae) is one of the species-richest and systematically the most complex genera of flowering plants. The genus traditional classification, beside Hieracium, included, among others, subgenus Pilosella, which is currently considered as separate genus. In folk medicine, application of some Hieracium s. str. species was reported for various respiratory, gastrointestinal, urogenital, and some skin disorders. The 28 species from the Balkan Peninsula were investigated, and majority was collected on the Mt Durmitor (Montenegro), where the greatest diversity of taxa of this genus was registered. In flowering aerial parts, composition of pharmaceutically significant secondary metabolites - flavonoids, phenolic acids, sesquiterpene lactones and triterpenes was established, and by multivariate statistical analysis their chemosystematic significance was demonstrated. Corresponding metabolites isolation was performed using column chromatography and semi-preparative liquid chromatography (LC-MS), identification using mass spectrometry, NMR spectroscopy and refractometry, and extracts comparative qualitative and quantitative analysis using LC-MS or gas chromatography (GC-FID-MS). In all 28 species, sesquiterpene lactones were identified for the first time. Three of them were previously undescribed proline conjugates. Sesquiterpene lactone-amino acid conjugates are quite rare in nature, and formerly were identified only in a few species of other Asteraceae genera. Results obtained by investigation of pharmacological activities (in vitro antioxidant, antimicrobial, cytotoxic, anticholinesterase, and in vivo antihyperalgesic and antiedematous), as well as safety profiles of selected, chemically characterized extracts and/or secondary metabolites, indicated the medicinal potential of the analysed plants and gave justification for further research aiming to find new natural medicinal raw materials.